Effectiveness of Video Based Learning and Demonstration Methods on Adolescents' Skills to Perform SADARI at SMPN 13 Jember - Isyfi Salwa Febriani; Imroatin Sholehah; Jimmy Opiyo (Universitas Satya Terra Bhinneka, 2025)
According to the 2018 Basic Health Research (Riskesdas), the prevalence of cancer in Indonesia reached 1.79% per 1000 population, up from 1.4% per 1000 population in 2013. The high number of breast cancer sufferers is actually caused by many who do not know about BSE so that it becomes a problem because they cannot understand the abnormalities in their breasts that should be detected as early as possible as a preventive measure. To determine the effectiveness of using the video-based learning and demonstration methods on the skills of adolescent girls in doing BSE. The research design used Quasi Experiment. The population was 60 female students of SMPN 13 Jember class VIII. Sampling used the cluster random sampling technique of 56 female students. The measuring instrument was a checklist and the analysis test was Chi Square. The skills of the Video Based Learning method were very poor 13 (43%), and very good 17 (57%). The skills of the Demonstration method were very poor 12 (40%) and very good 18 (60%). The analysis value with a p-value of 0.03 <α 0.05, which means there is a difference in skills. The Demonstration Method is more effective than the Video Based Learning method used for learning media because this method involves cognitive, affective and psychomotor abilities, so that health workers, especially midwives, can use the demonstration method as one of the counseling methods as a promotive and preventive effort.